Construction of a heat-inducible Escherichia coli strain for efficient de novo biosynthesis of l-tyrosine. (May 2020) - Xu, Sha; Wang, Qin; Zeng, Weizhu; Li, Youran; Shi, Guiyang; Zhou, Jingwen
Graphical abstract: Highlights: l -Phenylalanine and l -tryptophan biosynthesis pathways were blocked in E. coli . The global regulatory protein TyrR was deleted to increase l -tyrosine production. The pheA / tyrR double-gene deletion strain had the highest yield in shake flasks. The feedback resistance genes aroG fbr and tyrA fbr were heat-inducible expressed. Combination engineering of the genes increase the l -tyrosine titer to 55.54 g/L. Abstract: l -Tyrosine is an important amino acid widely used in food, agriculture, and pharmaceutical industries. However, the industrial application was severely constrained due to low production. To obtain the Escherichia coli mutant producing l -tyrosine in abundance, the heat-inducible expression vector carrying the two feedback resistance enzymes (3-deoxy-7-phosphoheptulonate synthase encoded by aroG fbr and chorismate mutase/prephenate dehydrogenase encoded by tyrA fbr ) were introduced into the phenylalanine-producing E. coli strain to enable it to synthesize l -tyrosine directly from glucose. Furthermore, the CRISPR-Cas9 technology was applied to eliminate l -phenylalanine and l -tryptophan pathways for their competition for the carbon flux. The global regulatory protein TyrR, which mediates the biosynthesis and transportation of aromatic amino acids, was also deleted to increase l -tyrosine production. Among the recombinant strains, the pheA/tyrR double-gene deletion strain had the highest yield of 5.84 g/L on shake flasks. The feeding strategies were then optimized in a 3-L fermentor. The pheA/tyrR double-gene deletion strain with the heat-inducible expression plasmid pAP- aroG fbr - tyrA fbr was able to produce 55.54 g/L l -tyrosine by fed-batch fermentation; the substrate conversion rate was 0.25 g/g. The recombinant strains constructed in this study could be an industrial platform for the microbial production of l -tyrosine directly from glucose.